Pertumbuhan dan Hasil Sorgum (Sorghum bicolor (L.) Moench) Pada Pemberian Pupuk Kandang Ayam dan Biochar Sekam Padi di Lahan Kering - Mapegau Mapegau; Mukhsin Mukhsin; Islah Hayati; Harry Setiawan (Jurnal Media Pertanian, 2023)
This research aimed to study the interaction between rice husk charcoal biochar and chicken manure on the growth and yield of sorghum plants on dry land. The study was conducted at the Teaching and Research Farm, Faculty of Agriculture, University of Jambi, with an elevation of ± 35 m above sea level. The study was conducted using a Randomized Block Design (RBD) with factorial patterns of 3 replications. The results showed that there was no interaction between rice husk biochar and chicken manure on the growth and yield of sorghum. Rice husk biochar had an effect on the growth and yield of sorghum plants, but chicken manure only had an effect on stem diameter.